Next-Generation Proteomics Reveals a Greater Antioxidative Response to Drought in Coffea arabica Than in Coffea canephora - Marques, Isabel (2022)
Funding Information: Fellowships from the Conselho Nacional de Desenvolvimento Científico e Tecnológico, Brazil (CNPq), and the Fundação de Amparo à Pesquisa do Estado de Minas Gerais, Brazil (FAPEMIG, project CRA-RED-00053-16), to F.M. DaMatta are also greatly acknowledged. Publisher Copyright: © 2022 by the authors. Licensee MDPI, Basel, Switzerland.